WSI Minimum Wage Report: Towards a new Minimum Wage Policy in Germany and Europe - Malte Lübker; Thorsten Schulten (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2022)
The past year has seen a much higher political pro file for the issue of minimum wages, not only in Germany, which has seen fresh initiatives to tackle low pay, but also in those many other countries in Europe that have embarked on substantial and sus tained increases in statutory minimum wages. One key benchmark in determining what should count as an adequate minimum wage is the threshold of 60% of the median wage, a ratio that has also played a role in the European Commission`s pro posals for an EU-level policy on minimum wages. This year`s WSI Minimum Wage Report highlights the feasibility of achieving minimum wages that meet this criterion, given the political will. And with an increase to exteuro 12 per hour planned for autumn 2022, Germany might now find itself promoted from laggard to minimum wage trailblazer.
Keywords: 330; Mindestlohn; Deutschland; EU-Staaten; Europa